2021
DOI: 10.2991/ahsr.k.210723.042
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Prevalence of Stunting in Young Children and Its Prevention

Abstract: Nearly 9 millions of Indonesian children suffer from stunting, and Indonesia is ranked the 5th in the world for the highest number of short children. Indonesia has made some progress towards achieving the target for stunting, but 30.8% of children under 5 years of age are still affected, which is higher than the average for the Asia region (21.8%). The study was aimed to know the risk factors related to the prevalence of stunting in children under 5 years old. The study used crosssectional study with sample ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Meanwhile, in some African and Asian countries (i.e. Nigeria, Indonesia and India), the prevalence of stunting in children under five years exceeds 30% (Menon et al, 2018;Olusanya et al, 2010;Hanifah et al, 2018) and some studies have even reported the prevalence of stunting to be as high as 52.1% (Linasari, 2021) and 80% (Kohlmann et al, 2021). In addition, a recent study among Southwest Ethiopian children also report the prevalence of stunting to be more than 30% (Zewdie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in some African and Asian countries (i.e. Nigeria, Indonesia and India), the prevalence of stunting in children under five years exceeds 30% (Menon et al, 2018;Olusanya et al, 2010;Hanifah et al, 2018) and some studies have even reported the prevalence of stunting to be as high as 52.1% (Linasari, 2021) and 80% (Kohlmann et al, 2021). In addition, a recent study among Southwest Ethiopian children also report the prevalence of stunting to be more than 30% (Zewdie et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Worms cause morbidity through a complex interaction between the host and specific parasites (Olds, 2013). Estimates indicate that more than 880 million children require treatment for helminthiasis, and the population at risk in Africa is about 350 million (WHO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Peran perawat komunitas pada tingkatan pencegahan penyakit salah satunya adalah pencegahan primer/peningkatan kesehatan (health promotion), yaitu peningkatan status kesehatan masyarakat melalui kegiatan, diantaranya pendidikan kesehatan (health education), penyuluhan kesehatan masyarakat (PKM) seperti penyuluhan tentang gizi, perbaikan status gizi masyarakat dan pengamatan tumbuh kembang anak (growth and development monitoring) dengan cara deteksi dini (Mediani, Nurhidayah, & Lukman, 2020).Upaya pencegahan stunting harus dimulai oleh ibu dari masa kehamilan terutama pada 1.000 hari pertama kehidupan, salah satunya adalah dengan pengetahuan dan sikap ibu tentang pencegahan stunting. Penguatan intervensi untuk meningkatkan pengetahuan dan sikap ibu tentang kesehatan dan gizi perlunya paket gizi (Pemberian Makanan) Tambahan, Vit A. Tablet Tambah Darah) pada ibu hamil dan balita, memahami pengasuhan dan pembinaan tumbuh kembang anak (Linasari, 2021)…”
Section: Pendahuluanunclassified